2019
DOI: 10.1017/dsi.2019.280
|View full text |Cite
|
Sign up to set email alerts
|

A Further Exploration of the Three Driven Approaches to Combinational Creativity

Abstract: Combinational creativity is a significant element of design in supporting designers to generate creative ideas during the early phases of design. There exists three driven approaches to combinational creativity: problem-, similarity- and inspiration-driven. This study provides further insights into the three combinational creativity driven approaches, exploring which approach could lead to ideas that are more creative in the context of practical product design. The results from a case study reveal that the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…In evaluating creative products, various methods are used, each with its strengths and weaknesses. These methods include the Consensual Assessment Techniques (CAT) [30], the Creative Product Analysis Matrix (CPAM) [28], and the Creative Product Semantic Scale (CPSS) [31]. When it comes to evaluating the teamwork of architectural students in terms of creativity, the CPSS is the most updated tool considered as a further development for the CPAM.…”
Section: Creativity and Idea Generation Styles Of Architectural Studentsmentioning
confidence: 99%
“…In evaluating creative products, various methods are used, each with its strengths and weaknesses. These methods include the Consensual Assessment Techniques (CAT) [30], the Creative Product Analysis Matrix (CPAM) [28], and the Creative Product Semantic Scale (CPSS) [31]. When it comes to evaluating the teamwork of architectural students in terms of creativity, the CPSS is the most updated tool considered as a further development for the CPAM.…”
Section: Creativity and Idea Generation Styles Of Architectural Studentsmentioning
confidence: 99%
“…By applying the “Explore function”, the designer could discover the knowledge concepts “C1”, “C2” and “C3” around the “Basic word” as denoted in Figure 7 . The “Search Path” function provides the paths, e.g., Path C1C2 between two terms “C1” and “C2” for combinational creativity ( Han et al 2019 ). This process can be iteratively applied to discover knowledge associations and paths such as “C3” and Path C1C3 .…”
Section: Demonstrationmentioning
confidence: 99%
“…For instance, Chan and Schunn (2015) found that far conceptual combinations, which are combinations of "source concepts that are very different from each other" (p. 104), do not necessarily lead directly to more creative concepts but "building on concepts that themselves build on far combination have more positive effects" (p. 104). Han, Park, Shi, Chen, and Childs (2017) proposed three approaches to foster combinational creativity, including problem-driven approach where a problem-solving idea plays the role of a bridge between the primary idea and the new target idea; similarity-driven approach where a similar representation works as an additive; and inspiration-driven approach where an inspirational idea stimulates a designer to generate new creative solutions. Malycha and Maier (2017) tested random-input technique to foster conceptual combination and found that conceptual combination enhances creativity when combined with knowledge activation.…”
Section: Combinational Ideation Process and Creativitymentioning
confidence: 99%